Analysis of Shrinkage Compensation Factor (SCF) of FDM uPrint SE for Accuracy Enhancement - Ranganathan, Rajesh; Ravi, T.; Pugalendhi, Arivazhagan (International Journal of Integrated Engineering, 2019)
This paper scrutinizes the shrinkage of a component manufactured using Additive Manufacturing (AM) and emphasizes mainly on the change in dimensions of an AM component after printing. The physical model can be easily manufactured by having the CAD data in STL format for real time AM. However, deviation of product size in CAD model transforming to physical model will be existing due to the deformation of the material mainly because of shrinkage. So here an analysis is carried out to find the optimal shrinkage compensation factor (SCF) of the part manufactured by Fusion Deposition Modelling (FDM) machine which uses ABS P430 as the base raw material. To achieve the latter a suitable model part is considered taking all the dimension and geometrical constraints which are essential for finding SCF and through regression analysis with the help of Co-ordinate Measuring Machine (CMM) and Solid Works modeling, SCF is calculated. Based on the experimental study, dimensional accuracy of the part significantly improved after applying the SCF value of 0.068% which is assumed to be constant in all directions.